Correction: Impact of immune evasion, waning and boosting on dynamics of population mixing between a vaccinated majority and unvaccinated minority - Fisman, David N.; Amoako, Afia; Simmons, Alison; Tuite, Ashleigh R. (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0297093.].